(untitled) (Eurasian Scientific Herald, 2024)
This article analyzes the views of scholars and educators on the scientific and theoretical aspects of teaching English to students through innovative technologies and interactive methods and the factors that stimulate their interest in learning the language, and their subjective attitudes.